Twenty-four-week oral dosing toxicities of Herba Siegesbeckiae in rats - Jia-Ying Wu; Yuen-Cheung Chan; Hui Guo; Ying-Jie Chen; Yu-Xi Liu; Hua Yi; Zhi-Ling Yu (BMC, 2020)
Abstract Background Herba Siegesbeckiae (HS), the dried aerial parts of Siegesbeckia orientalis L., S. pubescens Makino, or S. glabrescens Makino, is traditionally used for treating chronic diseases in China. However, there is no information about the chronic toxicity of HS. The objective of this study is to evaluate the 24-week oral dosing toxicities of HS aqueous extract (HSE) in rats. Methods S. orientalis-originated HS was reflux-extracted with distilled water. Sprague-Dawley rats were randomly divided into four groups, with 10 males and 10 females in each group. The rats were intragastrically administered with HSE at 5, 1.67 and 0.56 g/kg (experimental groups) or an equal volume of distilled water (control group), 6 days a week, for 24 weeks. The high dose of HSE (5 g/kg) was its maximum tolerated dose. Body weight was recorded every 2 days during the experimental period. Chemical, hematological and histopathological parameters, as well as organ weights, were measured at the end of the experiment. Results Decreased body weight gain; increased liver and lung relative weights; histopathological alterations in liver and lung tissues; elevated serum levels of alkaline phosphatase, aspartate aminotransferase, alanine aminotransferase and lactate dehydrogenase were found after HSE treatments. In liver tissues, HSE treatment upregulated levels of three pro-inflammatory cytokines: IL-6, IL-1β and TNF-α. In lung tissues, HSE treatment caused oxidative stress and activated mitogen-activated protein kinases (MAPKs). Conclusion Long-term oral administration of HSE caused toxicities in rats evidenced by decreased body weight gain, as well as liver and lung damage. Treatment-induced oxidative stress, inflammation and MAPK activation are involved in HSE's toxicities. Caution should be taken when using HS to treat chronic diseases.